Expression Profiles of miRNA Subsets Distinguish Human Colorectal Carcinoma and Normal Colonic Mucosa. Issue 3 (March 2016) - Pellatt, Daniel F; Stevens, John R; Wolff, Roger K; Mullany, Lila E; Herrick, Jennifer S; Samowitz, Wade; Slattery, Martha L
Abstract : OBJECTIVES: : MicroRNAs (miRNAs) are small, non‐protein‐coding RNA molecules that are commonly dysregulated in colorectal tumors. The objective of this study was to identify smaller subsets of highly predictive miRNAs. METHODS: : Data come from population‐based studies of colorectal cancer conducted in Utah and the Kaiser Permanente Medical Care Program. Tissue samples were available for 1, 953 individuals, of which 1, 894 had carcinoma tissue and 1, 599 had normal mucosa available for statistical analysis. Agilent Human miRNA Microarray V.19.0 was used to generate miRNA expression profiles; validation of expression levels was carried out using quantitative PCR. We used random forest analysis and verified findings with logistic modeling in separate data sets. Important microRNAs are identified and bioinformatics tools are used to identify target genes and related biological pathways. RESULTS: : We identified 16 miRNAs for colon and 17 miRNAs for rectal carcinoma that appear to differentiate between carcinoma and normal mucosa; of these, 12 were important for both colon and rectal cancer, hsa‐miR‐663b, hsa‐miR‐4539, hsa‐miR‐17‐5p, hsa‐miR‐20a‐5p, hsa‐miR‐21‐5p, hsa‐miR‐4506, hsa‐miR‐92a‐3p, hsa‐miR‐93‐5p, hsa‐miR‐145‐5p, hsa‐miR‐3651, hsa‐miR‐378a‐3p, and hsa‐miR‐378i. Estimated misclassification rates were low at 4.83% and 2.5% among colon and rectal observations, respectively. Among independent observations, logistic modeling reinforced the importance of these miRNAs, finding the primary principal components of their variation statistically significant ( P <0.001 among both colon and rectal observations) and again producing low misclassification rates. Repeating our analysis without those miRNAs initially identified as important identified other important miRNAs; however, misclassification rates increased and distinctions between remaining miRNAs in terms of classification importance were reduced. CONCLUSIONS: : Our data support the hypothesis that while many miRNAs are dysregulated between carcinoma and normal mucosa, smaller subsets of these miRNAs are useful and informative in discriminating between these tissues.